“I Helped Raise Them”: Gendered Expectations of Mothers and Their Children After Maternal Incarceration - Garcia-Hallett, Janet (Journal of contemporary criminal justice, 2025)
Individuals navigate through social expectations of designated roles across the different stages of childhood into emergent adulthood, and later in adulthood particularly as parents. Though roles and social expectations may shift as individuals age over time, gendered expectations may prevail in face of life-altering events. Through semi-structured interviews with three formerly incarcerated mothers and their four children, we provide in-depth case studies of mother–child experiences to comparatively explore how each group views their role and takes part in it during and after maternal incarceration. We found that social expectations of mothering trickle over onto the mothers’ children, particularly older girls and young women, as a means of compensating for mothers’ physical distance during incarceration and the socioeconomic setbacks that mothers experience after incarceration. Children’s experiences of maternal incarceration are shaped by the intersection of gender, age, and class as siblings support one another and their mothers in starting over and, vice versa, in the ways mothers try to start over based on where their children fall in these intersections.